How do dinosaurs play with their friends? - Yolen, Jane.; Teague, Mark (New York : Blue Sky Press, 2006)
Rhyming text and illustrations present some of the ways dinosaurs can play with their friends, from hogging the swings to sharing toys.
Cover title.
On board pages.
1.7
K-3
Keywords: Etiquette for children and teenagers -- Juvenile fiction; Play -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Behavior -- Fiction; Play -- Fiction; Dinosaurs -- Fiction; Stories in rhyme; Human behavior -- Fiction; Play -- Fiction; Dinosaurs -- Fiction; Stories in rhyme; Animals -- Habits and behavior -- Fiction; Play -- Fiction; Dinosaurs -- Fiction; Stories in rhyme